Effect of gamma irradiation on shelf life and quality of indigenous chicken meat: Irradiation on chicken meat (Journal of the Bangladesh Agricultural University, 2019)
The experiment was conducted on fresh indigenous chicken meat treated with 0 (non-irradiated), 1, 2 and 3 kGy  60Co gamma irradiation and stored for 0, 30 and 60 days at -20ºC to investigate the effects on proximate components, sensory attributes, and physicochemical, biochemical and microbial changes in meat quality. Data were analyzed under 4x3 factor CRD design of experiment in GLM procedure of SAS statistical package. The results showed that irradiation groups had significantly (p